2020
DOI: 10.3389/fneur.2020.608444
|View full text |Cite
|
Sign up to set email alerts
|

The ADNP Syndrome and CP201 (NAP) Potential and Hope

Abstract: Activity-dependent neuroprotective protein (ADNP) syndrome, also known as Helsmoortel-Van Der Aa syndrome, is a rare condition, which is diagnosed in children exhibiting signs of autism. Specifically, the disease is suspected when a child is suffering from developmental delay and/or intellectual disability. The syndrome occurs when one of the two copies of the ADNP gene carries a pathogenic sequence variant, mostly a de novo mutation resulting in loss of normal functions. Original data showed that Adnp+/− mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Most drugs targeting microtubules are anticancer agents that may also possess anti-neurodegenerative and antiviral effects ( Hung and Fu, 2017 ; Fernandez-Valenzuela et al., 2020 ; Tsai et al., 2020 ; Sirakanyan et al., 2021 ). Many of these drugs demonstrated beneficial effects in animal models, however those tested in humans are few and include TPI-287 and NAP (Davunetide CP201), an intranasal neuropeptide (NAPVSIPQ)(NAP) (NCT01966666) ( Gozes, 2020 ). These MSAs have not reached the clinic, however, activity-dependent neuroprotective protein (ADNP), derived from NAP, remains a potential hope and is scheduled for future clinical trials ( Varidaki et al., 2018 ; Al-Horani and Kar, 2020 ; Santiago-Mujika et al., 2021 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%
“…Most drugs targeting microtubules are anticancer agents that may also possess anti-neurodegenerative and antiviral effects ( Hung and Fu, 2017 ; Fernandez-Valenzuela et al., 2020 ; Tsai et al., 2020 ; Sirakanyan et al., 2021 ). Many of these drugs demonstrated beneficial effects in animal models, however those tested in humans are few and include TPI-287 and NAP (Davunetide CP201), an intranasal neuropeptide (NAPVSIPQ)(NAP) (NCT01966666) ( Gozes, 2020 ). These MSAs have not reached the clinic, however, activity-dependent neuroprotective protein (ADNP), derived from NAP, remains a potential hope and is scheduled for future clinical trials ( Varidaki et al., 2018 ; Al-Horani and Kar, 2020 ; Santiago-Mujika et al., 2021 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%
“…In conclusion, PACAP and NAP play a key role in retinal physiopathology; however, while PACAP's half-life is a minute or shorter, NAP's half-life is relatively long for a peptide, half an hour. NAP has previously been used in clinical trials showing safety and tolerability as well as efficacy increasing cognitive functions and protecting activities of daily living in mild cognitive impairment patients and schizophrenia patients, respectively (Gozes 2020). Overall, the evidences reported suggest that PACAP and NAP could be considered good candidates for therapeutic approach to DR. cell-specific markers in ischemia-induced retinal degeneration.…”
Section: Discussionmentioning
confidence: 96%
“…The protective action of NAP was demonstrated in many in vitro and in vivo studies; it prevents apoptotic cell death in neurons exposed to different kinds of stress such as glucose deprivation and β-amyloid or tetrodotoxin treatment, and in a rat model of cerebral ischemia and severe head injury (Bassan et al 1999;Leker et al 2002;Beni-Adani et al 2001;Zaltzman et al 2005;Zemlyak et al 2007;Jehle et al 2008;Gozes et al 2008;Belokopytov et al 2011). Noteworthy, the chemical structure of this small fragment peptide allows it to penetrate into cell membrane and by binding to microtubules it protects astrocytes and neurons (Divinski et al 2004;Oz et al 2012;Ivashko-Pachima et al 2017;2019a and2019b;2020;Gozes et al 2015;Grigg et al 2020). Furthermore, it has been demonstrated that NAP provides significant neuroprotection also in a diabetes rat model (Idan-Feldman et al 2011) and it has been also showed that NAP regulates PAC1 expression (Kapitansky et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some of the first concerns regarding the complex interaction between genotype and the conducting laboratory were raised in the field of rodent behavioral phenotyping (Crabbe et al 1999). While mouse and rat models may predict the human situation, such as the case of activity-dependent neuroprotective protein (ADNP) and the potential of its fragment as a drug (reviewed in Gozes, 2020), the utility of any findings critically depends on their replicability in other laboratories (Kafkafi et al, 2018; Voelkl et al, 2018). A similar concern arises regarding the interaction between the conducting laboratory and novel pharmacological treatments (e.g., Rossello et al, 2019) that are of vital importance for translational research, leading to novel drug developments.…”
Section: Introductionmentioning
confidence: 99%